β-Lactoglobulin heat-induced aggregates as carriers of polyunsaturated fatty acids - Perez, Adrián Alejandro (2014)
The aim of this work was to obtain heat-induced β-lactoglobulin (BLG) aggregates in order to test them as carriers of a model polyunsaturated fatty acid (PUFA), linoleic acid (LA). BLG aggregates were obtained at 85 °C by varying the heating time (0–60 min) and pH of protein dispersion (6.5–7.5). Aggregates were characterised by intrinsic and extrinsic fluorescence and surface hydrophobicity (S0). Binding experiments were conducted by fluorescence spectroscopy. Results showed increased BLG aggregate S0 values which could strongly depend on the pH of aggregate formation. Aggregates obtained at pH 6.5 showed the greatest S0 values, so they could find application as LA carriers. Nevertheless, conjugation of LA to BLG aggregates showed complex behaviour depending on the aggregate producing conditions (pH, heating time and/or combination). The LA binding properties of BLG aggregates were not linked to their hydrophobic characteristics, suggesting that conjugation could require the structural preservation of the LA binding site.